Noise Evaluation of the Finalization Phase Construction Project of X Hospital - Rahman, Ari; Susanto, Harits Bimo; Qonitan, Fatimah Dinan; Aryani, Eri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
This research aimed to identify and assess the noise levels at a construction project within X Hospital's B2nd, 5th, 8th, and 9th floors. The study employed a sound level meter according to the Indonesian National Standard (SNI) 7231:2009 to measure noise intensity in the workplace. The primary sources of high noise levels were jackhammers, hammers, portable ventilators, iron-cutting machines, and pipe-cutting tools, with corresponding readings of 148, 114, 95.4, 85, and 85 dB, respectively. To mitigate the potential risks of excessive noise, recommendations were made based on the risk control hierarchy outlined in the Occupational Health and Safety Assessment Series (OHSAS) 18001:2007 for Occupational Health and Safety Management Systems, including equipment substitution, administrative controls, and the use of appropriate personal protective equipment (PPE), such as earplugs. The effectiveness of earplugs, with a noise reduction ratio (NRR) of 30 dB, was highlighted for reducing noise levels below the threshold limit value (TLV) and ensuring worker safety.